Encaminhamento por hardware em redes definidas por software : avaliação experimental utilizando NETFPGA - Eller, Ana Carolina Ewald (2016)
Computer networks have become an essential part of the infrastructure of our society, however, the initial design of traditional networks cannot meet the requirements of all these applications because many were not even imagined. As a result, there is a network environment with little support and flexibility to the new requirements. In this context, there was then a promising concept of programmable networks called Defined Networks Software (SDN - Software Defined Network). SDN separates the data plane from the control plane enabling developers to program the network according to their application needs. In addition, it made possible the implementation and testing in real environments, technological innovations for the environment networks without, for that, rely on the equipment manufacturers. This paper proposes the use of NetFPGAs as routing tool in an SDN controlled by an OpenFlow controller to decrease the path a packet from its source to its destination. Furthermore, it is proposed to use NetFPGA OpenFlow for implementing multiple paths with load balancing. It will be evaluated yet, the influence of packet switching in the flow charts comparing a protocol which uses routing tables for (OpenFlow) with one that does not use tables for this purpose (KeyFlow).